PENGARUH HARGA, KREATIVITAS, DAN INOVASI TERHADAP MINAT BELI PELANGGAN (STUDI KASUS PADA PELANGGAN TOKO SHEREN HIJAB BENGKULU) - Gustiarini, Endah; Ekowati, Sri (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2021)
This study aims to determine the effect of price, creativity, and innovation on customer buying interest (a case study of the customer of the Sheren Hijab Bengkulu shop), either partially or simultaneously. There are several factors that will be discussed in this research, including Price, Creativity, and Innovation. The object of this research is the customer of the Sheren Hijab Bengkulu shop, which amounts to 75 people. In this research the authors use the method of data collection by means of observation, distributing questionnaires or questionnaires. Data analysis techniques used in this study, using instrument test, classical assumption test, respondent response analysis, multiple linear regression analysis, determinant coefficient, and hypothesis testing.Â The results showed that Price has a positive effect on Customer Purchase Intention (Case Study on Customers of the Sheren Hijab Bengkulu Shop). This means that if this is in accordance with the quality of the products provided at the Sheren Hijab Bengkulu Shop, this is felt according to the value of the benefits obtained, of course it is not a problem for customers to decide to make a purchase. Creativity has a positive influence on Customer Purchase Interest (Case Study of the Sheren Hijab Bengkulu Customer Shop). This means that if creativity is further enhanced, customers' buying interest will be even higher for the products offered by the Sheren Hijab Bengkulu Shop. Then the innovation variable shows a positive influence on customer buying interest (Case Study on the customer of the Sheren Hijab Bengkulu Store). This means that if product innovation is further enhanced, customers' buying interest will also increase. So, from the results of the research that has been done, it can be concluded that Price, Creativity, and Innovation have a partial or simultaneous effect on Customers' Purchase Intention (Case Study on Customers of the Sheren Hijab Bengkulu Shop).Â Keywords: Price, Creativity, Innovation, and Purchase Interest